1961
DOI: 10.1152/ajplegacy.1961.200.6.1191
|View full text |Cite
|
Sign up to set email alerts
|

Size of microspheres passing through pulmonary circuit in the dog

Abstract: After injection of microspheres into the pulmonary artery approximately 50% of spheres 2.8–4.0 µ in diameter can be found in the systemic circuit during the first circulation, but only 6% of those 8 µ or larger get through the pulmonary circuit when compared with simultaneously injected tagged erythrocytes. If vessels are impeding the flow of spheres and are circular in cross section, then more than half of the erythrocytes must be distorted while passing through the pulmonary circuit. A continuous infusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

1964
1964
1998
1998

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…Ring et al [31] and Kaihara et al [17] demonstrated that the mi crocirculation of the lung almost completely trapped 15 ±5 (SD) mi crospheres injected into a peripheral vein. Ohlsson et al [23,25,26] demonstrated that also the microcirculation of the liver in dogs will trap almost all 15 ±5 (SD) ¿on spheres injected into the portal vein and the hepatic artery.…”
Section: Discussionmentioning
confidence: 99%
“…Ring et al [31] and Kaihara et al [17] demonstrated that the mi crocirculation of the lung almost completely trapped 15 ±5 (SD) mi crospheres injected into a peripheral vein. Ohlsson et al [23,25,26] demonstrated that also the microcirculation of the liver in dogs will trap almost all 15 ±5 (SD) ¿on spheres injected into the portal vein and the hepatic artery.…”
Section: Discussionmentioning
confidence: 99%
“…In the animal experiments, droplets whose diameter was the same or less than the pulmonary capillaries would have passed through the pulmonary vascular bed by the time the animal was killed. Large droplets that passed through arteriovenous anastomosis would not be counted, too, but evidence has been presented that this is of little consequence during the first circulation (11). In the final analysis, the true size of vessels occluded by the droplets might be smaller than the measured droplet diameters, and hence the latter should be considered an approximation only.…”
Section: Discussionmentioning
confidence: 99%
“…After injection of glass microspheres into the dog pulmonary artery, approximately 50 percent of spheres 2.8 -4.0 ~m in diameter could be found in the systemic circuit during the first circulation, but only 6 percent of those spheres eight ~m or larger got through the pulmonary circuit when compared with simultaneously injected tagged erythrocytes (83).…”
Section: The Lumentioning
confidence: 95%